Crop Production and Global Environmental Issues 2015
DOI: 10.1007/978-3-319-23162-4_17
|View full text |Cite
|
Sign up to set email alerts
|

Plant Responses and Tolerance to High Temperature Stress: Role of Exogenous Phytoprotectants

Abstract: Among the abiotic stresses high temperature stress is one of the most detrimental stresses threatening higher plant productivity and survival throughout the world. Each degree Celsius increase of average growing season temperature may decrease crop yield and affect plant distribution. On the other hand, global average temperatures are supposed to increase from 1.8 to 4.0 °C or higher by 2100 as compared to the 1980-2000 average. Plants are intimidated by adverse effects of high temperature stresses. Protein de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 210 publications
1
19
0
Order By: Relevance
“…Temperature stresses that are induced by low or high temperatures inhibit water uptake, which immediately leads to a slowing down of leaf growth. This observation was correlated with a loss of turgor in leaf cells and an adjustment of the osmoticum, which enables cells to regain turgor [40]. AGP are well known for their water-holding properties [41].…”
Section: Discussionmentioning
confidence: 99%
“…Temperature stresses that are induced by low or high temperatures inhibit water uptake, which immediately leads to a slowing down of leaf growth. This observation was correlated with a loss of turgor in leaf cells and an adjustment of the osmoticum, which enables cells to regain turgor [40]. AGP are well known for their water-holding properties [41].…”
Section: Discussionmentioning
confidence: 99%
“…High temperature severely alters the plant physiological processes including germination, photosynthesis, respiration, transpiration, partitioning of dry matter, etc. [87]. In addition, HT results in enzyme inactivation, protein denaturation, disruption of proteins and membranes which ultimately affects plant growth [88,89].…”
Section: Extreme Temperaturesmentioning
confidence: 99%
“…Similarly, Reddy, Reddy, and Hodges () found that higher temperature will increase the cotton canopy photosynthetic rate when alternating temperatures was 30/22°C. Higher temperature will increase the effective accumulated temperature, leading to faster growth rate in critical plant phenological stages (Whittaker, ), and affect tissue nutritional composition and secondary metabolites (Nahar et al., ). In addition, plant leaf nutrition also influences insect feeding and growth patterns.…”
Section: Discussionmentioning
confidence: 99%